1998
DOI: 10.21273/jashs.123.5.875
|View full text |Cite
|
Sign up to set email alerts
|

(E)-2-Hexenal Can Stimulate Botrytis cinerea Growth in vitro and on Strawberries in vivo during Storage

Abstract: Some plant-derived natural volatile compounds exhibit antifungal properties and may offer an opportunity to control the causes of postharvest spoilage without affecting quality of, or leaving a residue on, fresh produce. The natural wound volatile (E)-2-hexenal has exhibited significant antifungal activity in earlier studies, but effects on spore germination and mycelial growth have not been separated, nor has the inhibitory mode of action been determined. To determine the ef… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
43
1
1

Year Published

2003
2003
2020
2020

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 67 publications
(50 citation statements)
references
References 0 publications
5
43
1
1
Order By: Relevance
“…The efficacy of some compounds depended on fungal growth stage: P. expansum conidial germination was more sensitive to trans ‐2‐hexenal concentration than mycelial growth, while the opposite was found for the phenols, carvacrol and eugenol, and for the aldehydes, trans ‐cinnamaldehyde and citral. These findings are in agreement with those reported by Fallik et al . (1998) for trans ‐2‐hexenal against B. cinerea.…”
Section: Discussionsupporting
confidence: 94%
“…The efficacy of some compounds depended on fungal growth stage: P. expansum conidial germination was more sensitive to trans ‐2‐hexenal concentration than mycelial growth, while the opposite was found for the phenols, carvacrol and eugenol, and for the aldehydes, trans ‐cinnamaldehyde and citral. These findings are in agreement with those reported by Fallik et al . (1998) for trans ‐2‐hexenal against B. cinerea.…”
Section: Discussionsupporting
confidence: 94%
“…M. laxa mycelial growth was more sensitive to the phenols carvacrol and eugenol and to the aromatic aldehydes trans-cinnamaldehyde and panisaldehyde than was conidial germination, whereas the opposite was found for the aliphatic aldehydes trans-2-hexenal and hexanal and the ketone 2-nonanone. A greater sensitivity of conidia than mycelia to trans-2-hexenal vapors also was found in B. cinerea (16). Bioassay results confirmed the antifungal activity against M. laxa by trans-2-hexenal vapor treatment (20 µl/liter in peach, nectarine, and plum and 10 µl/liter in apricot), with efficacy varying from 42.6 to 97.1%.…”
Section: Discussionsupporting
confidence: 55%
“…Previous studies on B. cinerea with trans-2-hexenal (16) and on Cladosporium herbarum with carvacrol (1) showed that these compounds cause severe damage to fungal membranes and cell walls, which leads to morphological deformations and collapse and deterioration of conidia or hyphae. The fungicidal activity of trans-2-hexenal and citral aldehydes may be ascribed to the high electrophilic properties of the carbonyl group adjacent to the double bond that make these compounds particularly reactive with nucleophiles, such as protein sulfhydryl and amino groups of the pathogen (2).…”
Section: Discussionmentioning
confidence: 99%
“…Trans-2-hexenal effectively reduced blue mold infections and patulin content in "Conference" pears and apples (Neri et al 2006), and the shelf life of apple slices is extended by inhibiting Pichia subpelliculosa infection (Corbo et al 2000). The concentration dependent inhibition of growth of B. cinerea have been observed that the inhibition was evident with 1 μM or higher of trans-2-hexenal (Fallik et al 1998).…”
Section: Introductionmentioning
confidence: 95%